TYPES OF DISCIPLINARY RESPONSIBILITY: GENERAL AND SPECIAL DISCIPLINARY RESPONSIBILITY - Karimjonov Mukhammadamin Mukhammadliyevich (Journals Park Publishing, 2022)
The article examines the institution of disciplinary responsibility as one of the types of legal responsibility, reveals its tasks and functions. Labor discipline ensures the fulfillment of the necessary socio-economic, organizational and technical conditions for normal work, stimulation and encouragement of conscientious work, the implementation of penalties for employees who have violated labor duties. The basis for bringing an employee to disciplinary responsibility is the commission of a disciplinary offense by the employee. Disciplinary responsibility is a legal responsibility arising for the commission of a disciplinary offense by an employee and expressed in the application of a disciplinary penalty to an employee who has committed a disciplinary offense. The types of disciplinary responsibility are general and special disciplinary responsibility.The article analyzes сoncept of labor discipline, disciplinary offence, systematic and a single flagrant violation by the worker of his labour duties, peculiarities of the application of disciplinary sanctions. The main differences between the special disciplinary responsibility and the general are noted, namely: 1) the circle of persons to whom it applies 2) types of disciplinary sanctions 3) the number of persons who may not apply disciplinary sanctions 4) the procedure for applying the penalties 5) the procedure for appealing disciplinary penalties. Proposals for improving national legislation for disciplinary responsibility are provided.
Keywords: employee, employer, disciplinary responsibility, special disciplinary responsibility